WAWASAN DUNIA KRISTEN DAN PANGGILAN GEREJA: ARAH GEREJA MODERN BERMISI - Tony Salurante (Sekolah Tinggi Teologi Simpson, 2021)
Christian Worldview is the way we see Christianity as a complete unity that hooks up with each other. Every human being has a worldview that consciously or not, affects the beliefs of life. This fundamental thing is not easy to understand but it controls all aspects of human life. In the midst of a changing modern world it proves how Christian worldview becomes the antithesis of secular worldview and other religions. This research explains the problem and is associated with church callings. These problems raise various conflicts of ideas and beliefs that affect each other. On the one hand the church has a calling to be salt and light of the world. On the other hand, the church is also commanded to not be similar to the world. The purpose of this research is to show how the philosophical concept of Christianity as a way of church views can play a significant role for the church calling, so that the church can distinguish and know the values that influence another worldview. By utilizing a philosophical-systematic approach it produces answers to research questions. An approach with Christian worldview is able to encourage the church to proclaim the truth in every aspect of life effectively and provide the right perspective for the belivers in the modern age to be a means of God's mission.